ANALISIS PEMASARAN IKAN KOI (KASUS DI DESA BABAKAN, KECAMATAN CISEENG, KABUPATEN BOGOR) - Elvin Elvin; Wahyu Budi Priatna (Forum Agribisnis, 2018)
Koi is a prospective fishery commodity that make a positive contribution to Indonesia National GDP. Subdistrict Ciseeng especially in Babakan Village became one of the areas that make a positive contribution because there is a koi farmers, but has a different price level koi farmers with the consumer level. The purpose of this research is to analyze the institution, functioning, marketing channels and efficiency of marketing channels koi. Methods of data collection using purposive sampling to farmers and marketing agencies using snowball sampling. The results showed marketing agencies involved include farmers, village merchants, merchant shops and suppliers with functions exchange, physical and facility in nine koi marketing channels in Babakan Village. The efficiency of marketing channels occurs in channels VII because it has a lower marketing margins, the farmer's share is higher and the ratio of benefits to costs relatively with sales volume 210 tail.